Construction Shortfall and Forensic Investigation on Soft Ground. Issue 1 (July 2016) - Saravanan, M; Ibrahim, B N
Abstract: Recently, numerous construction activities performed on soft ground have undergone various kind of failures. Some of the failures were due to lack of understanding the nature of soft ground, inadequate site investigation data, adaptation of inappropriate type of ground improvement techniques or foundation system. Couple with inadequate desk study carried out to the historical condition of the site, chronological of activities carried out within the site prior to construction. Hence coordinated approach required to be executed for field investigation works with proper supervision would be the key to prevent any design or construction related failure in the future. This paper addresses some of shortfalls related to design and construction failures in soft ground.